2006
DOI: 10.2519/jospt.2006.2198
|View full text |Cite|
|
Sign up to set email alerts
|

Use of Pulsed Shortwave Diathermy and Joint Mobilization to Increase Ankle Range of Motion in the Presence of Surgical Implanted Metal: A Case Series

Abstract: Study Design: Case series. Background: Traditionally, all forms of diathermy have been contraindicated over metal implants. There is a lack of research-based evidence for harm regarding the use of pulsed shortwave diathermy (PSWD) over orthopaedic metal implants. Because PSWD is an effective modality for deep heating, we investigated whether ankle range of motion (ROM) could improve with the cautious use of PSWD and joint mobilizations, despite orthopaedic metal implants being in the treatment field. Case Desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 35 publications
2
28
0
1
Order By: Relevance
“…Similar studies involving only SWT that were conducted on either asymptomatic subjects (12,14,15,31) or patient groups (10,32,33) have been reported previously. However, to our knowledge this will be the first in vivo study that investigated the deep physiological responses to RF exposure below the shortwave frequency band.…”
Section: Introductionsupporting
confidence: 61%
“…Similar studies involving only SWT that were conducted on either asymptomatic subjects (12,14,15,31) or patient groups (10,32,33) have been reported previously. However, to our knowledge this will be the first in vivo study that investigated the deep physiological responses to RF exposure below the shortwave frequency band.…”
Section: Introductionsupporting
confidence: 61%
“…The elbow should extend to a full AROM (08) as measured by a goniometer. 1 Many [1][2][3][4][5][6] are of the opinion that using heat in concert with joint mobilizations can increase accessory and physiologic movements. In 2010, I…”
mentioning
confidence: 99%
“…The higher residual temperature that the Megapulse II produced is important because it allows the clinician a greater potential to elongate the tissues when a mechanical stress is applied and a longer stretching window in which to apply the mechanical stresses, such as stretching or joint mobilizations. 18 Researchers 13,21,22 have found that these high-temperature increases when followed by joint mobilizations increase range of motion in the shoulder, elbow, knee, and ankle. ReBound diathermy was inadequate to heat the tissues to a level of vigorous heating.…”
Section: Discussionmentioning
confidence: 99%
“…10 Given that the initial change in tissue-temperature increase is important for producing various physiologic effects, the decay in the temperature increase is also vitally important to a clinician when trying to increase joint range of motion. 7,21,22 A diathermy device that initially causes a 48C tissue-temperature increase, producing more potential to elongate the tissues, and then has a slower temperature decay will give a clinician a longer stretching window, during which joint mobilizations and stretching will be more effective. 1 After the 30-minute treatment, ReBound diathermy produced a slower temperature decay than the Megapulse II diathermy.…”
Section: Discussionmentioning
confidence: 99%